Coastal Abrasion Disaster Threat Analysis in North Galesong District, Takalar Regency - Chaerul, Muhammad; Firdaus, Firdaus (Universitas Ibn Khaldun Bogor, 2023)
Coastal damage due to abrasion can interfere with residents' livelihoods, especially those who work as fishermen. Beaches that experience abrasion will result in more severe beach damage if not addressed. Coastal dynamics caused by wave activity, tides, currents, and human activities cause shoreline changes. This study aims to determine the coastal abrasion disaster threat level in North Galesong District, Takalar Regency. The analytical method used is the analysis of coastal abrasion threat index data in coastal areas, including oceanographic data, namely wave height and current speed, ecological data, mangrove vegetation density, the physical environment, and the shape of the coastline and beach characteristics. Analysis of the data using the analysis table of disaster threat assessment issued by the Head of BNPB Regulation No. 2 of 2012 concerning General Guidelines for Disaster Risk Assessment. The study results have a high category of coastal erosion threat in the coastal area of Galesong Utara District, which is found in all coastal village areas. The high category level represents the high potential threat of coastal abrasion to the incidence of casualties and material losses on the coast of North Galesong District. It is necessary to build structural mitigation to maintain coastal stability in the form of longshore sedimentation retaining structures, abrasion absorbers, and, breakwater structures to reduce the rate of coastal abrasion.